2015
DOI: 10.1109/tvlsi.2014.2311234
|View full text |Cite
|
Sign up to set email alerts
|

A Synergetic Use of Bloom Filters for Error Detection and Correction

Abstract: Bloom filters (BFs) provide a fast and efficient way to check whether a given element belongs to a set. The BFs are used in numerous applications, for example, in communications and networking. There is also ongoing research to extend and enhance BFs and to use them in new scenarios. Reliability is becoming a challenge for advanced electronic circuits as the number of errors due to manufacturing variations, radiation, and reduced noise margins increase as technology scales. In this brief, it is shown that BFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The Morton filter, an approximate set membership data structure, is used to overcome the problem. It is an improved data structure, when compared with bloom [55] and cuckoo filters [56], in terms of space-efficient insertion, deletion, and lookup. An algorithm named as identify_positions (Algorithm 1) has been designed, and it explains the algorithm that can detect the position or location of modified or tampered data in the hierarchical block.…”
Section: Methodsmentioning
confidence: 99%
“…The Morton filter, an approximate set membership data structure, is used to overcome the problem. It is an improved data structure, when compared with bloom [55] and cuckoo filters [56], in terms of space-efficient insertion, deletion, and lookup. An algorithm named as identify_positions (Algorithm 1) has been designed, and it explains the algorithm that can detect the position or location of modified or tampered data in the hierarchical block.…”
Section: Methodsmentioning
confidence: 99%
“…Reviriego et al [29] talk about the application of bloom filter. It is shown that BFs can be used to detect and correct errors in their associated data set.…”
Section: Related Workmentioning
confidence: 99%
“…There are also some other papers about application of bloom filter in network such as Space-Code bloom filter by Kumar et al [32], and Fast Dynamic Multiple-Set Membership Testing by Hao et al [33]. Duan et al [29] proposed a distributed public cloud storage system that allows users to store files named as CSTORE. It is based on a three-level mapping hash method.…”
Section: Related Workmentioning
confidence: 99%
“…A Bloom filter [17] is a multi-bit probabilistic data structure used for membership querying to determine whether an input is the element included in a given set. Bloom filters have been applied to many network applications due to their space-efficient attributes [18][19][20][21] and hardware-friendly features [22][23][24][25][26].…”
Section: Bloom Filtermentioning
confidence: 99%